A Widening Gap In Economic Crisis And Opportunities: A Perspective Of Migration And Hiv From Dadeldhura, Far-West Of Nepal - Jha, CK (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: A cross-sectional study was undertaken to explore socio-economic conditions of inhabitants from Dadeldhura district in Far-West Nepal. Methodology: The study examined chances of migration to India for earning, and then possible risks of HIV transmission in migrants. Results: It was found that most of the respondents have insuffi cient food supplies, which led to a large number of economically productive populations to migrate India for earning. Although the level of knowledge on HIV/AIDS was high in the respondents, they also had several confusions. The cultural restrictions forbid them to talk about the issues related to sexuality or to acquire relevant information. Conclusion: As an implication, they remained unaware of the threat of HIV transmission despite the fact that some of them engaged in unsafe sexual behaviours. Provisions of information through peer networks seem to be effective to promote safer sexual behaviors in migrant populations. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5887 SAARCTB 2011; 8(1): 15-19